Gambling with virtue : Japanese women and the search for self in a changing nation - Rosenberger, Nancy Ross (Book collections on Project MUSE., 2001)
Annotation Gambling with Virtue rings with the voices of women speaking openly about their struggle to be both modern and Japanese in the late twentieth century. It brings to the fore the complexity of women's everyday lives as they navigate through home, work, and community. Meanwhile, women fashion selves that acknowledge and challenge the social order. Nancy Rosenberger gives us their voices and experiences interspersed with introductions to public ideas of the last three decades that contribute significantly to the opportunities and risks women encounter in their journeys. Rosenberger uses the stage as a metaphor to demonstrate how everyday life requires Japanese women to be skilled performers. She shows how they function on stage in their accepted roles while effecting small but significant changes backstage. Over the last thirty years, Japanese women have expanded their influence and extended this cultural process of multiple arenas to find compromises between the old virtues of personhood and new ideals for self. They conform, maneuver, and make choices within these multiple stages as they juggle various concerns and desires. By the 1990s their personal choices have made a difference, calling into question the very nature of these multiple arenas.